Sexual harassment and sexual assault in the Western Australian mining industry: a qualitative examination of the perceptions of key stakeholders - Vrankovich, Sarah; Burns, Sharyn; Yam, Cheryl M. H.; Parker, Sharon K.; Hendriks, Jacqueline (Frontiers in Public Health, 2024)
Introduction The prevalence, pervasiveness, and minimization of sexual harassment and sexual assault (SHSA) within the Western Australian mining industry has been revealed in recent Australian reports and inquiries. However, there remains a gap in scholarship focusing on SHSA within the mining sector, specifically that engages with mining employees to understand this issue. Methods This study aimed to fill this gap by exploring the experiences and perspectives of Western Australian mining employees in relation to SHSA. Through qualitative research methods, stakeholders (n = 30) from various industry roles (e.g., front-line operations, administrative staff) participated in semi-structured interviews. A deductive thematic analysis was conducted to analyze the data. Results The study revealed diverse perspectives of SHSA among participants, highlighting how this issue is understood, addressed, and discussed within the workplace. While some participants recognized positive shifts in workplace culture, it became apparent that additional efforts are needed to tackle the underlying and persistent factors that contribute to sexism, misogyny, and, ultimately, SHSA. Participants shared their perspectives regarding strategies and initiatives that could effectively combat SHSA within the industry. Discussion This study constitutes a significant contribution to the limited body of research on SHSA in the Western Australian mining sector, offering valuable insights and recommendations for future prevention initiatives.